2003
DOI: 10.1128/mcb.23.19.6739-6749.2003
|View full text |Cite
|
Sign up to set email alerts
|

Defective Brain Development in Mice Lacking the Hif-1α Gene in Neural Cells

Abstract: Hypoxia-inducible factor 1␣ (HIF-1␣) is essential for vascular development during embryogenesis and pathogenesis. However, little is known about its role in brain development. To investigate the function of HIF-1␣ in the central nervous system, a conditional knockout mouse was made with the Cre/LoxP system with a nestin promoter-driven Cre. Neural cell-specific HIF-1␣-deficient mice exhibit hydrocephalus accompanied by a reduction in neural cells and an impairment of spatial memory. Apoptosis of neural cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
205
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(219 citation statements)
references
References 38 publications
5
205
4
Order By: Relevance
“…These data in conjunction with our results showing no direct involvement of HIF-1a in the development of the central dopaminergic system in all oxygen conditions in vivo strongly suggest a role of HIF-1a in mediating postdevelopmental regeneration and/ or survival of dopaminergic neurons [25]. However, other reasons for the discrepancies in the morphology of the dopaminergic system between the two HIF-1a CKO models could be the different genetic manipulation (knock out of exon 2 as used by Milosevic et al [25] and exon 13-15 in the present study [35]) or differences in the genetic background.…”
Section: /Nurr1contrasting
confidence: 40%
See 1 more Smart Citation
“…These data in conjunction with our results showing no direct involvement of HIF-1a in the development of the central dopaminergic system in all oxygen conditions in vivo strongly suggest a role of HIF-1a in mediating postdevelopmental regeneration and/ or survival of dopaminergic neurons [25]. However, other reasons for the discrepancies in the morphology of the dopaminergic system between the two HIF-1a CKO models could be the different genetic manipulation (knock out of exon 2 as used by Milosevic et al [25] and exon 13-15 in the present study [35]) or differences in the genetic background.…”
Section: /Nurr1contrasting
confidence: 40%
“…For HIF-1a studies, the Hif-1a gene was knocked out by crossing HIF-1a flox/flox mice [35] (generously provided by Shuhei Tomita, MD, PhD) with a conditional transgenic mouse strain expressing the Cre recombinase gene under the control of the promotor of the Nestin gene, which is typically upregulated in all neural precursors during embryonic development. Further details on the generation and genotyping of Hif-1a CKO embryos have been described previously [36].…”
Section: Animals and Breedingmentioning
confidence: 99%
“…Two of the genes induced by IL-1␤ in our study, HIF-1␣ and VEGF-A, were of particular interest in the context of BBB breakdown. Both are involved in developmental angiogenesis, they are known to be functionally linked, and animal studies have shown the importance of the HIF-VEGF axis in vascular development (23,24,29,50).…”
Section: Discussionmentioning
confidence: 99%
“…In the developing embryo, the HIF-VEGF pathway is known to act as a critical mechanism in the induction of vascular plasticity that is associated with angiogenesis (23,24,50,51). Changes in vascular permeability are the first detectable signs of new lesion formation in MS (4), and we hypothesized that IL-1␤-induced reactivation of the HIF-VEGF axis in astrocytes might act as a significant contributing factor in the pathogenesis of these events.…”
Section: Expression Of Hif-1␣ Vegf-a and Vegfr2/flk-1 In Ms Lesionsmentioning
confidence: 99%
“…Although one could conclude that no major role for HIF exists in the embryonic ventricular myocardium, confounding factors in gene-inactivation studies may include family member redundancy, cell and physiologic compensations and adaptations within the embryo, issues in the timing of gene inactivation relative to morphogenesis, and efficiency of inactivation of the gene and its protein product. In a study using a different floxed HIF-1␣ allele, neural-specific inactivation of HIF-1␣ by using nes-Cre resulted in a much greater reduction in vessel density (80%) in the brain's ventral cortical plate associated with apoptosis of the neuronal cells (104). As a reduction in VEGF was found in the brains of these mice, this suggests that brain parenchymal hypoxic induction of HIF-1 and VEGF is required to generate a vascular supply to this organ.…”
Section: Vasculogenesis and Angiogenesis The Formationmentioning
confidence: 99%